Hybrid area exploration–based mobility‐assisted localization with sectored antenna in wireless sensor networks. (13th November 2019) - Nagaraju, Shamanth; V, Sreejith; Gudino, Lucy J.; Kadam, Bhushan V.; C. K., Ramesha; Rodrigues, Joseph
Summary: In common practice, sensor nodes are randomly deployed in wireless sensor network (WSN); hence, location information of sensor node is crucial in WSN applications. Localization of sensor nodes performed using a fast area exploration mechanism facilitates precise location‐based sensing and communication. In the proposed localization scheme, the mobile anchor (MA) nodes integrated with localization and directional antenna modules are employed to assist in localizing the static nodes. The use of directional antennas evades trilateration or multilateration techniques for localizing static nodes thereby resulting in lower communication and computational overhead. To facilitate faster area coverage, in this paper, we propose a hybrid of max‐gain and cost‐utility–based frontier (HMF) area exploration method for MA node's mobility. The simulations for the proposed HMF area exploration–based localization scheme are carried out in the Cooja simulator. The paper also proposes additional enhancements to the Cooja simulator to provide directional and sectored antenna support. This additional support allows the user with the flexibility to feed radiation pattern of any antenna obtained either from simulated data of the antenna design simulator, ie, high frequency structure simulator (HFSS) or measured data of the vector network analyzer (VNA). The simulation results show that the proposed localization scheme exhibits minimal delay, energy consumption, and communication overhead compared with other area exploration–based localization schemes. The proof of concept for the proposed localization scheme is implemented using Berkeley motes and customized MA nodes mounted with indigenously designed radio frequency (RF) switch feed network and sectored antenna. Abstract : In this paper, we propose the directional antenna support for the Cooja simulator, which takes into account the side lobes and back lobes of the directional antenna to provide a realistic support. A hybrid area exploration–based localization scheme is employed for mobile anchor node–assisted localization. In this scheme, the mobile anchor nodes mounted with the sector antenna evades the need for multiple beacons from localizing a static node. A single beacon with MA node's coordinates and antenna orientation information is sufficient to localize the static nodes using simple trigonometric functions, thus resulting in lower communication and computation overhead.